Corpus-Based Research on Terminology of Turkish Lexicography(CBRT-TURKLEX) - Boz, Erdoğan; Bozkurt, Ferdi; Doğru, Fatih (Lexikos, 2018)
In this paper, we introduce an ongoing lexicographic corpus project. The Center for Lexicography, abbreviated as SÃ–ZMER, was established under the aegis of Eskisehir Osmangazi University to support lexicographical projects. SÃ–ZMER decided to initiate a corpus-based Turkish lexicography project. This project will be the first stage of the endeavour aimed at preparing a specialized dictionary for Turkish lexicography. The primary aim of the project is to prepare an electronic corpus for researchers of Turkish lexicography. The secondary aim of the project is to obtain a word list of Turkish lexicographic terms. This paper presents a description of the process of data collection and the methodology employed for building a specialized corpus. The study contains an outline of the project background, needs, problems, and the phases of corpus building.